Aligning Human Resource Strategy with Business Objectives: A Case Study Approach to Maximizing Organizational Performance - Neil Gaiman, Ray Bradbury (International Journal of Innovative and Applied Finance, 2021)
login and register and pay the fees to get an open access to content